Drug induced toxic epidermal necrolysis. Case report - Solano-Dazzarola, Paola Andrea (2023)
Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are considered two mucocutaneous disorders associated with rare drug reactions within clinical practice, whose severity depends on the extent of the lesions in both skin and mucous membranes, and the time elapsed from symptom onset and prodrome to diagnosis. In recent decades, understanding of the disease pathogenesis has increased and the association between toxicity mediated by cytotoxic T lymphocytes and genes of human leukocyte antigens (HLA) has been described; however, many of the factors associated with the development of the disease remain under investigation, such as TEN induced by viral infections. The aim of this research is to document a case of TEN in an adult male patient with systemic involvement after starting treatment with amoxicillin.